PENGARUH SELEKSI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. MOTORINDO PERKASA RAYA - Loren Arifin; Hendry Hendry; Dewi Mariana; Veranovelia Veranovelia; Rita Rita (JURNAL PROINTEGRITA, 2019)
Employees’ performance is an action taken by employees in carrying out the work given by the company. Many things influence employee performance including selection and training. This study aims at examining and analyzing the influence of selection and motivation on employees’ performance at PT. Motorindo Perkasa Raya Medan both partially and simultaneously.The theory used is a theory regarding employees’ selection, motivation and performance.The method used is a quantitative approach with quantitative descriptive research and it is descriptive explanatory. The method of data collection was done by doing interviews and questionnaires. The method of data analysis used is multiple linear regression. The population is all employees; the total number is 35 people. Sampling was taken by a saturated sampling technique. The results of the study proves that partially selection (2,960) and motivation (6,911) have a positive and significant effect on employees’ performance with a significant level of <0.05. Simultaneously selection and motivation have a positive and significant effect on employee performance, with the results of Fcount (48,351) > Ftable (3.29) a significant level <0.05. The conclusion of the result of this study is that selection and motivation influence employee performance at PT Motorindo Perkasa Raya both partially or simultaneously.